Utilization of Big Data Analytics in Understanding Climate Change Patterns: Latest Trends and Findings on Climate Patterns in Indonesia - Sopian, Abu; Setiadi, Dedi; Fitriani, Novita (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Climate change has become a global concern. In Indonesia, a deep understanding of climate change patterns is increasingly important in planning effective mitigation and adaptation measures. In this study, we explore the utilization of big data analytics to understand climate change patterns and identify trends findings related to climate patterns in Indonesia based on variables such as temperature, humidity, rainfall, and wind speed. Data used were collected from satellite observations, weather stations from 2010 to 2020. Purpose this study aims to explore the utilization of big data analytics in understanding climate change patterns in Indonesia, with a focus on identifying trends and recent findings in climate patterns. Methodology–We applied big data analytics techniques such as descriptive statistical analysis, spatial regression modeling, and cluster analysis to identify climate change patterns and recent trends in Indonesia. Findings–Through big data analysis, we successfully identified significant climate change patterns in Indonesia. Practical implications the findings of this study can provide a better understanding of climate change dynamics in Indonesia, serving as a basis for decision-making in natural resource management, disaster risk mitigation, and climate change adaptation strategies at both regional and national levels and can serve as a reference for researchers.